Citicoline in Non–arteritic Anterior Ischemic Optic Neuropathy: Pattern Electroretinography review - Valen Chia; M. Sidik; Syntia Nusanti (Majalah Oftalmologi Indonesia, 2022)
This study aims to assess 1000 mg citicoline each day given for 60 days on chronic phase NAION (non–arteritic anterior ischemic optic neuropathy) patients. Double masked randomized clinical trial divided the patients into 2 groups: citicoline group (C–NAION) and placebo group (P–NAION). Analysis was done in 17 patients in each group. There were increament of ? amplitude P50 30 days in C–NAION group (0,775±2,6 µV) and ? amplitude N95 60 days in C–NAION group (–0,356±2,992 µV) but statistically insignificant compared to P–NAION. Age has a good correlation with ? amplitude P50 (r = –0.517; p = 0.002). Subjects with 1 risk factor experienced a higher ? amplitude of P50 than the subjects with more than 1 risk factor (1.856 ± 2.121 ?V vs –0.26 ± 2.45; p = 0.025). Citicoline did not show any changes in Retinal Ganglion Cell Thickness. There were improvement of ? mean deviation 60 days in C–NAION group (3,13±6,467 dB), but statistically insignificant compared to P–NAION. Citicoline tends to increase the ? amplitude of P50, N95 and mean deviation in chronic phase NAION. Age and the number of risk factors affects the increase of ? amplitude P50.